(untitled) (Research, Society and Development, 2021)
The discovery of the possibility of predicting the development of breast cancer has possible, so a woman can perform a genetic test and fi nd out what her probability of developing breast cancer, however, the discovery of the probability does not mean mastectomy is indicated. In this regard, the work aims to clarify what breast cancer is, how it develops, which genes are involved in the neoplastic process and what forms of prevention, as well as explaining what is mastectomy and what are its types, addressing the positives and negatives for the lives of patients who undergo such surgery. It is a descriptive narrative research with a qualitative approach, of literary analysis through the databases: virtual libraries (SciELO - Scientifi c Electronic Library Online (http // www.scielo.org / index.php); LILACS (Latin American and Caribbean Literature in Health Sciences); VHL - Virtual Health Library (http // www.base. Bvs.br/index.php); reference books; reliable websites. There was no year restriction for selected publications that involved the studied topic.Conclusion: Like other breast cancer prevention methods, mastectomy is a measure that has its positive and negative points, but in short it is an effective preventive measure, but more studies are needed to solidify the practices of this method as prevention.